Taking agri-food sector financing commercial: Some change is needed and welcomed - Francis, Diana (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The document discusses the need for changes in the commercial financing of the agri-food sector. It highlights the importance of the involvement of commercial financial sector in the development of the agri-food industry, especially in Caricom. The launch of a new financial product by the Republic Bank Trinidad and Tobago targeting stakeholders in the agri-food value chain is mentioned, which is seen as a positive development. The importance of engaging more commercial financial institutions in funding the agricultural sector to drive transformation, innovation, and competitiveness is emphasized. Additionally, the need to overcome existing barriers in financing the agri-food sector to achieve sustainable development and reduce food imports in the region is mentioned.